PKM Inovasi Sistem Rotasi Tanam Menuju IP400 Sistem Padi-Jagung-Melon-Semangka “PAJAMEKA” - Masluki, Masluki; Mutmainnah, Mutmainnah; Firdamayanti, Erni (Universitas Muhammadiyah Sidenreng Rappang, 2023)
Abstract. Community service activities (PKM) with the theme Planting Rotation System Innovation Towards IP400 Rice-Corn-Melon-Watermelon System